After stress comes relax(ation). (17th November 2015) - Isa, Lucio
Abstract: Viscoelastic materials take a finite time to relax and dissipate stress and this time scale is directly connected to the microstructure of the material itself. In their paper, Gomez-Solano and Bechinger (2015 New J. Phys. 17 103032 ) perform 'miniaturized' mechanical tests on a range of viscoelastic materials by dragging a micron-sized bead across them using optical tweezers. Upon switching off all the external forces, they watch the bead recoil to its original position and by tracking its motion they pinpoint the relaxation time of the material. These experiments open up a new range of possibilities to characterize stress relaxation at the microscale just by watching it.